(untitled) (LACCEI, 2024)
In recent decades, the deglaciation of tropical snow-capped mountains represents a reduction in water storage for populations, economic activities, and ecosystems that depend on their waters, especially in arid areas such as the foothills of the Ampato mountain range in the department of Arequipa, in the Andes of southern Peru, being necessary to determine the factors that drive it, such as its relationship with global warming and other relevant meteorological phenomena. In this sense, the objective of the research was to determine the relationship between the glacier loss area in the Coropuna and Solimana stratovolcanoes with the variation of temperatures and precipitations registered in the nearest meteorological stations during the period 1986 to 2022. For this, the surface of the glaciers was determined with multispectral Landsat images of each year, using the normalized differential water index calculation in the QGIS software, to correlate with the main elements of the climate of the area. As results of the analysis, a 64% reduction in the glacier area was determined, presenting a stronger correlation with the increase in maximum temperature, compared to weaker relationships with a stable minimum temperature and strongly fluctuating rainfall with a slightly increasing trend. It is concluded that there is a marked trend of glacier mass loss, reducing the Coropuna mountain to less than half of the maximum extension it presented in 1989, being more accentuated in the Solimana mountain that maintains only 4% of the area it had that same year. Likewise, in the previous or initial period of a strong El Niño-Southern Oscillation event, there is a temporary recovery of the glacier area, but it is followed by a period with a strong loss of glacier mass due to an increase in temperature and liquid precipitation during the most intense stage of the event.